PERHITUNGAN TARIF SEWA GEDUNG GRAHA DEWARUCI DENGAN METODE COST PLUS PRICING PENDEKATAN FULL COSTING - Nilna Faizah Madaniah; Fitri Hardiyanti; Irma Rustini Aju (Proceeding Maritime Business Management Conference, 2023)
Surabaya State Shipbuilding Polytechnic is a polytechnic engaged in shipping. The status of PPNS which was originally a Work Unit (Satker) changed to a Public Service Agency (BLU). The recording of PPNS into BLU aims to improve services to the community. In this case, some facilities at PPNS can be used or rented by the general public, one of which is Graha Dewaruci. At this time, the determination of the rental rate has not been calculated properly, so an accurate rate calculation is needed by considering and paying attention to other variable indicators to produce an appropriate rate. To calculate the rental rate in this study, using the Cost Plus Pricing method of the Full Costing approach and the policies related to this calculation are decided by the PPNS asset manager who is an educational institution under the auspices of the government, so in the process of calculating the rental rate, it still uses the policies stipulated in government regulations to produce the Graha Dewaruci Building rental rate of IDR 16,320,000.